The Theatre of Imagining A Cultural History of Imagination in the Mind and on the Stage - Kallenbach, Ulla (Springer International Publishing, 2018)
This book is the first comprehensive analysis of the fascinating and strikingly diverse history of imagination in the context of theatre and drama. Key questions that the book explores are: How do spectators engage with the drama in performance, and how does the historical context influence the dramaturgy of imagination? In addition to offering a study of the cultural history and theory of imagination in a European context including its philosophical, physiological, cultural and political implications, the book examines the cultural enactment of imagination in the drama text and offers practical strategies for analyzing the aesthetic practice of imagination in drama texts. It covers the early modern to the late modernist period and includes three in-depth case studies: William Shakespeare's Macbeth (c.1606); Henrik Ibsen's A Doll's House (1879); and Eugène Ionesco's The Killer (1957).